2015
DOI: 10.1016/j.simyco.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integrated phylogenetic classification of theTremellomycetes

Abstract: Families and genera assigned to Tremellomycetes have been mainly circumscribed by morphology and for the yeasts also by biochemical and physiological characteristics. This phenotype-based classification is largely in conflict with molecular phylogenetic analyses. Here a phylogenetic classification framework for the Tremellomycetes is proposed based on the results of phylogenetic analyses from a seven-genes dataset covering the majority of tremellomycetous yeasts and closely related filamentous taxa. Circumscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
356
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(394 citation statements)
references
References 143 publications
17
356
0
1
Order By: Relevance
“…N. antarcticus, N. consortionis , and N. vishniacii ) and Himalayan ( N. bhutanensis ) cryptococci grouped in a clade with N. albidus (Takashima and Nakase 1999). This grouping has been confirmed by numerous other studies including the recent work of Liu et al (2015a, 2015b) who showed that N. friedmannii, N. antarcticus, N. vishniacii and N. bhutanensis are in the albidus clade of the Filobasidiales based on a seven-gene (RPB1, RPB2, TEF1, CYTB, and 3 rDNA genes) phylogeny. Also relevant to the present study, Vimercati et al (2016) showed that the isolate from Volcán Llullaillaco (discussed below) forms a monophyletic clade with N. friedmannii based on long-read 18S environmental sequences (1739 bp, JX099190) from Llullaillaco (Lynch et al 2012).…”
Section: Phylogeny Of the Naganishia Cladesupporting
confidence: 74%
“…N. antarcticus, N. consortionis , and N. vishniacii ) and Himalayan ( N. bhutanensis ) cryptococci grouped in a clade with N. albidus (Takashima and Nakase 1999). This grouping has been confirmed by numerous other studies including the recent work of Liu et al (2015a, 2015b) who showed that N. friedmannii, N. antarcticus, N. vishniacii and N. bhutanensis are in the albidus clade of the Filobasidiales based on a seven-gene (RPB1, RPB2, TEF1, CYTB, and 3 rDNA genes) phylogeny. Also relevant to the present study, Vimercati et al (2016) showed that the isolate from Volcán Llullaillaco (discussed below) forms a monophyletic clade with N. friedmannii based on long-read 18S environmental sequences (1739 bp, JX099190) from Llullaillaco (Lynch et al 2012).…”
Section: Phylogeny Of the Naganishia Cladesupporting
confidence: 74%
“…Two novel species represented by strains TSN-538 and TSN-649 (forest soils, Hainich National Park) were placed in the genus Piskurozyma in the phylogenetic analysis performed by Liu et al (2015) and in the present study (Fig. 5).…”
Section: Resultsmentioning
confidence: 53%
“…Following the "one fungus = one name" principle, systematics of basidiomycetous yeasts was recently revised and unified with the classification of filamentous (often sexual) fungi (Liu et al 2015;Wang et al 2015). Also, the polyphyletic genera Cryptococcus and Rhodotorula were restricted to the lineages, where the type species belong.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these pathogenic species, T. asahii, T. asteroides, T. faecale, T. inkin, T. coremiiforme, T. dermatis, and T. mycotoxinivorans are the main species associated with deep-seated infections (2,4). Recently, based on multiple-gene sequence analysis, Trichosporon taxonomy has been reassessed, and new genera have been proposed for the monophyletic clades, which include Trichosporon, Cutaneotrichosporon, and Apiotrichum for pathogenic species (5). These genera are intrinsically resistant to echinocandins, and resistance to other antifungal classes has been described (2,4).…”
mentioning
confidence: 99%